Literacy (Dis)Orientations in a Secondary Classroom: Possibilities and Limits of an Intersectional LGBTQ+‐Inclusive Curriculum. Issue 1 (22nd November 2022) - Schey, Ryan
Abstract: Drawing from a yearlong literacy ethnography conducted at a high school in a Midwestern U.S. city, this article extends queer literacies and queer pedagogies scholarship by exploring the frictions and resonances between strategies of inclusion and queering. While inclusion strategies emphasize using expanded representations of sexuality and gender, such as of LGBTQ+ life, queering approaches often trouble inclusion through, for instance, questioning normativities and epistemologies and embracing partiality, uncertainty, and crisis in learning. To unpack interconnections between inclusion and queering, I present an ethnographic case of a lesson in a sophomore humanities course, focusing on the teacherly moves of an English language arts educator leading an instructional conversation about a nonfiction article describing intersections among sexuality, gender, race, ethnicity, and class with respect to food insecurity. Engaging Ahmed's (2006) queer theorization of orientations, I develop the heuristic of literacy (dis)orientations to describe the layered mixture of classroom literacy performances challenging and reifying oppressive values regarding intersections among sexuality, gender, race, ethnicity, and class. The teacher disoriented students away from (homo)normativities regarding knowledge of LGBTQ+ communities and reoriented them toward and around nuanced, intersectional understandings of queer and trans life. However, these anti‐oppressive possibilities were limited by orientations around a banking model of education and binaries. This ethnographic case suggests that educators sanctioning literacy orientations toward intersectional LGBTQ+‐inclusive curriculum presents possibilities for liberatory social change insofar as they disorient students away from education‐as‐banking and epistemological binaries and reorient them around alternative ways of knowing, specifically intersectionality as a queering epistemology. Abstract : Drawing from a yearlong literacy ethnography conducted at a high school in a Midwestern U.S. city, this article extends queer literacies and queer pedagogies scholarship by exploring the frictions and resonances between strategies of inclusion and queering. While inclusion strategies emphasize using expanded representations of sexuality and gender, such as of LGBTQ+ life, queering approaches often trouble inclusion through, for instance, questioning normativities and epistemologies and embracing partiality, uncertainty, and crisis in learning.